Influence of features of the transport network pattern on the haul cycle length between its nodes on the example of the transport network of Ukraine - Dolya, Constantine; Lyfenko, Sergey; Nesterenko, Sergey; Vyatkin, Konstantin (Technology audit and production reserves, 2017)
The object of research is the road network based on the example of the existing network in Ukraine. During the audit of the main parameters affecting the performance of the transport systems, the mileage of vehicles is determined. It is established that road networks stipulate not only the actual distance between its nodes, but also the potential parameters of the characteristics of traffic of vehicles over the network. Disadvantages of road networks are their cost, limited bandwidth and pattern. In the course of the research of the road network pattern, the methods of network analysis and graph theory are used. A matrix of the shortest distances between regional centers of Ukraine is calculated. As a result of the research it is shown that transportation to Kherson, Odesa or Simferopol is carried out on routes that are on average 44 %, 46 % and 64 % more than possible if there is an appropriate road network. It is determined that the quality of the transport network pattern can be described by the straightness coefficient. The definition of the straightness coefficient of the road network is given. Calculations of the values have established that in the considered network this coefficient takes values from 0.24 to 0.64. The investigated road network offers the organization of communication between the cities of Kharkiv and Cherkasy with the straightness coefficient of the road network – 0.6.